Anticancer effects of washed-dehydrated solar salt doenjang and its metabolites - So-Young Lee; Geun-Hye Hong; Kun-Young Park (Journal of Ethnic Foods, 2024)
Abstract In this study, the anticancer effect of doenjang according to the type of salt was investigated. Three samples were prepared: doenjang made with purified salt, doenjang made with generally manufactured solar salt, and doenjang made with washed and dehydrated solar salt (WDSD). In mice in which colon cancer was induced with azoxymethane/dextran sodium sulfate, doenjang made with solar salt, especially doenjang made with washed and dehydrated solar salt, was found to have a much higher colon cancer inhibition effect. WDSD significantly promoted the mRNA expression of apoptosis-related factors such as Bcl-2–associated X protein (Bax) and caspase 9 and the cell cycle arrest-related factors p53 and p21, and conversely significantly reduced the mRNA expression of apoptosis inhibitors such as B-cell lymphoma-2 (Bcl-2) (p < 0.05). Additionally, metabolites were investigated to determine which substances in WDSD exhibit this anticancer effect. As a result, the contents of isoflavone and soyasaponin B in the form of aglycons such as genistein, daidzein, and glycitein, which are known to have anticancer and anti-inflammatory properties, were found to be significantly high. Therefore, the results confirmed that doenjang prepared with washed and dehydrated solar salt has superior anticancer potential against colon cancer, and that various active ingredients contribute to the improvement of this functionality.